2018
DOI: 10.1007/s13258-018-0678-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of favorable alleles for yield and yield components by association mapping in upland cotton

Abstract: Association mapping based on linkage disequilibrium provides a promising tool for dissecting the genetic basis underlying complex traits. To reveal the genetic variations of yield and yield components traits in upland cotton, 403 upland cotton accessions were collected and analyzed by 560 genome-wide simple sequence repeats (SSRs). A diverse panel consisting of 403 upland cotton accessions was grown in six different environments, and the yield and yield component traits were measured, and 560 SSR markers cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…In addition, SSR markers NAU4951, NAU5013, NAU5195, NAU5148, NAU5260, NAU5088, and NAU5017 were mainly associated with yield quality traits, including HF, NB, SB, PH, LP. These identified associations for different fiber and yield quality traits in domesticated upland cotton, along with those reported in previous studies, add toa rich cluster of yield and fiber quality QTLs ( Cai et al., 2014 , Adhikari et al., 2017 , Ademe et al., 2017 , Dong et al., 2018a , Dong et al., 2018b ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, SSR markers NAU4951, NAU5013, NAU5195, NAU5148, NAU5260, NAU5088, and NAU5017 were mainly associated with yield quality traits, including HF, NB, SB, PH, LP. These identified associations for different fiber and yield quality traits in domesticated upland cotton, along with those reported in previous studies, add toa rich cluster of yield and fiber quality QTLs ( Cai et al., 2014 , Adhikari et al., 2017 , Ademe et al., 2017 , Dong et al., 2018a , Dong et al., 2018b ).…”
Section: Discussionsupporting
confidence: 82%
“…The major target traits of cotton during the breeding process are quantitative; thus, phenotypic variation of each trait is directly or indirectly affected by that of other traits ( Huang et al., 2018 , Keerio et al., 2018 , Wen et al., 2018 ). Numerous QTL mapping studies aimed at improving cotton fiber quality and yield traits have been previously reported ( Mei et al., 2013 , Adhikari et al., 2017 , Wang et al., 2017a , Wang et al., 2017b , Dong et al., 2018a , Dong et al., 2018b ). In this study, a total of 16 SSR markers for yield and fiber quality traits were detected.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are all located in chromosomal regions, which show a strong association with important agronomic traits and they can thus be considered as suitable target genes for future breeding programs. We calculated the phenotypic effect of favorable alleles, as described by Dong et al [59] to show that they affected grain yield only slightly but had much larger effect on thousand kernel weight, spike length and leaf greenness. On the other hand, alleles that contribute to an improvement in thousand kernel weight and leaf greenness also have pleiotropic effects thereby decreasing plant height, peduncle length and canopy temperature under stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years, association mapping as an important method for the identi cation of complex quantitative traits has been widely used in cotton for various traits including salt tolerance [35][36][37][38][39][40]. Jia et al [21] identi ed 3 simple sequence repeats (SSR) markers signi cantly associated with the relative survival rate under salt stress through association mapping methods using 323 G. hirsutum germplasms.…”
Section: Discussionmentioning
confidence: 99%